Nature in virtual reality improves mood and reduces stress : evidence from young adults and senior citizens - Chan, Sarah Hian May (2021)
Large populations worldwide have been deprived from nature experiences due to mass quarantines and lockdowns during the COVID-19 pandemic, and face a looming mental health crisis. Virtual reality offers a safe and practical solution to increase nature exposure. This research examined the effects of virtual nature using a within-subject design with young adults (Study 1) and senior citizens (Study 2). Results from the young adult sample showed that walking in a virtual forest reduced negative affect due to enhanced nature connectedness, and reduced stress measured by heart rate. Consistently, the senior citizen sample reported improved positive affect due to enhanced nature connectedness after the virtual nature walk. Our findings unveil the underlying mechanism of how virtual nature may improve psychological well-being and demonstrated how virtual nature can be used as an intervention to promote mental health.